Evaluación del potencial energético de la biomasa, para el aprovechamiento de la generación de gas metano (CH4), en la granja avícola Cynthia Elizabeth de la ciudad de Pujilí en el año 2016., Propuesta de diseño de un biodigestor” - Hidalgo Osorio, William Armando (2017)
The aim of this research is to evaluate the energy potential of the biomass generated at the Cynthia Elizabeth poultry farm in Pujili city, for the production and use of methane gas CH4 as alternative energy, for which the biomass generated in the Poultry farm was placed in an experimental biodigestor degrading the biomass in absence of oxygen O2 in a determined time obtaining the biogas, for this we applied field research techniques, bibliographical and experimental, that allowed to obtain results of characterization of the biomass , Biol, biogas, biogas production results and, finally, biogas application results. With these results we made a proposal to design a biodigester for the production and use of methane gas as an alternative energy. Obtaining as a result for each 45m3 of biomass generated in the poultry farm produces